Understanding the properties of operations: a cross-cultural analysis. Issue 1 (2nd January 2021) - Ding, Meixia; Li, Xiaobao; Hassler, Ryan; Barnett, Eli
Abstract : This study examines how sampled Chinese and U.S. third and fourth grade students ( N China  = 167, N US  = 97) understand the commutative, associative, and distributive properties. These students took both pre- and post-tests conducted at the beginning and end of a school year. Comparisons between students' pre- and post-tests within and across countries indicate different learning patterns. Overall, Chinese students demonstrate a much better understanding than their U.S. counterparts. Among these properties, the associative and distributive properties appear to be most challenging, especially for the U.S. students. By the end of grade 4, some Chinese students demonstrate explicit understanding of the associative and distributive properties across tasks; almost no U.S. students achieve a comparable level of understanding on these properties. Student understanding in different contexts also reveals cross-cultural differences. Chinese students tend to reason upon concrete contexts for sense-making, which is rare with U.S. students. Finally, the Chinese student sample shows clear growth of understanding across grades, but this is not seen in the U.S. sample. This understanding gap between the two countries is found to dramatically increase over time. Implications are discussed.